Market outlook for the capesize sector from 2010 to 2015 - Ho, Hwee Ming. (2011)
This study investigates the key drivers of the Capesize freight market and performs a holistic fundamental analysis to derive a direction in which the Capesize bulk carrier freight market will take in the period of 2010 and 2015. The study comprises of 3 Volumes; with Volume 1 focusing on demand drivers, Volume 2 focusing on supply drivers, and Volume 3 evaluating the profitability and possible strategies applicable to invest in the Capesize market over a 5 year period. The objective of this paper, Volume 2, is to examine the supply side drivers and its effects on the future Capesize freight market, given demand growth projected in Volume 1. The drivers discussed in this paper include ship financing, projected scrap age, port congestion, fleet age profile and pressure of oversupply of tonnage. Ship financing climate is found out to be encouraging of fleet growth despite unfavorable market signals. Projected scrap age is projected to reduce from current 27.3 years old to 25 due to pressures from regulatory bodies and oversupply situation. Port congestion at iron ore ports has minimal impact on Capesize freight market. Conclusively, the discussion presented in this paper presents a poor market outlook for Capesize sector up till 2014 when commodity demand growth spurt close up the gap of oversupply in tonnage. Given that this forecast only takes into account supply side factors, this paper is to be studied along with Volumes 1 and 3 of the paper to achieve an accurate representation of the market position this project concludes.